The Byzantine East and Bulgaria – The Eastern Armies of Byzantium in the Wars Against the First Bulgarian Empire (680–1018) - Antonov, Symeon (Studia Ceranea, 2024)
This article deals with the engagement of the Byzantine eastern troops in the wars the empire waged against Bulgaria from the late seventh until the early eleventh centuries. To this end, both narrative and sphragistic sources are examined, and the data obtained are compared in order to get as full as possible picture of the composition of the Byzantine armies which fought against early medieval Bulgaria. Here the subject is analysed mainly from the Byzantine perspective. This helps outline certain trends in the development of the Byzantine army and the general Byzantine military strategy when Bulgaria is concerned.